2023
DOI: 10.1108/sampj-05-2022-0260
|View full text |Cite
|
Sign up to set email alerts
|

External corporate governance and assurance of corporate social responsibility reports: evidence from China

Abstract: Purpose This paper aims to verify whether the legitimate pressure of external forces on heavily polluting firms’ corporate social responsibility (CSR)-related behaviors affect firms’ assurance strategy in the Chinese context. The authors argue that, under external pressure, as a source of legitimacy, the assurance over CSR reports allows the business behaviors of heavy polluters to be recognized by society. Design/methodology/approach This paper sampled listed heavy polluters in China from 2011 to 2018 and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 162 publications
(255 reference statements)
0
7
0
Order By: Relevance
“…Two recent studies investigate Chinese companies' decisions regarding whether to provide assurance, Khalid et al (2022) and Liu et al (2023). The uptake on CSR assurance in China has been exceptionally low.…”
Section: Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies investigate Chinese companies' decisions regarding whether to provide assurance, Khalid et al (2022) and Liu et al (2023). The uptake on CSR assurance in China has been exceptionally low.…”
Section: Determinantsmentioning
confidence: 99%
“…The uptake on CSR assurance in China has been exceptionally low. Liu et al (2023) examine the effects of external corporate governance on companies' assurance decisions for a sample 4217 company‐years of heavy polluting companies from 2011 to 2018 (the assurance rate for the sample is only one percent). Five dimensions of external corporate governance are measured: (1) law and regulation (laws and their enforcement vary across provinces and municipalities in China), (2) various markets (e.g., monitoring by institutional investors, intensity of corporate control and managerial labor markets, and product market competition), (3) providers of capital market information (e.g., analyst following and ESG rating agencies), (4) external accounting, financial and legal firms (e.g., audit fees, Big 4 auditor, number of professional lawyers), and (5) the media (e.g., media coverage).…”
Section: Determinantsmentioning
confidence: 99%
“…Drivers encompass investor requisites for transparency, the management of environmental liabilities as a risk mitigation strategy, and the pursuit of competitive advantages through sustainability leadership [ 2 ]. However, while green accounting and environmental reporting offer numerous benefits, they also come with challenges and obstacles [ 14 ]. These impediments may comprise the absence of standardized reporting frameworks, intricacies in data collection, and apprehensions regarding the divulgence of sensitive ecological data [ 18 ].…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Studies have revealed that businesses in developing economies particularly Sub-Saharan Africa often report less environmental information than those in developed economies despite the rising trend toward green accounting [ [9] , [10] , [11] ]. Earlier studies focused on the interplay between financing decisions and sustainability performance Wahyuningrum, Budihardjo [ 12 , 13 ], financing choices and environmental information disclosure Liu, Li [ 14 , 15 ], ownership structure and corporate social responsibility [ 16 ], ownership diversity and environmental performance Gonzalez and Peña-Vinces [ 17 , 18 ], and corporate governance and ESG performance [ 19 ]. Moreover, most prior studies are based on institutional theory, legitimacy theory, agency theory, and resource dependence theory to investigate the relationship between financing decisions and sustainable development Zhang, Tang [ 20 ], as well as financing decisions and sustainable performance [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investors and financial institutions are increasingly considering environmental, social, and governance (ESG) factors, including CSR disclosure, in their investment decisions [50,51]. Consequently, companies with strong corporate governance practices and robust CSR disclosure are often regarded as less risky and more attractive to investors, resulting in improved access to capital [52]. This improved access to capital leads to a lower cost of capital, better credit ratings, and increased investment opportunities, all of which can positively impact a company's financial performance.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%